MENINGKATKAN HASIL BELAJAR SISWA KELAS XI IPS 2 MELALUI METODE PEMBELAJARAN BERBASIS PEMECAHAN MASALAH, PADA KONSEP MENGELOLA KARTU AKTIVA DI SMA NEGERI 1 KERAMBITAN TAHUN PELAJARAN 2016/2017 - Yusniawati, Gusti Ayu Arry (LPPM IKIP PGRI Bali, 2019)
This study aims to describe and analyze the effectiveness of learning method with Troubleshooting against Accounting based to the learning achievement of student Grade XII IPS 2 SMA Negeri 1 Kerambitan in the academic year 2016/2017. Students who were being the research subject have low understanding to the basic concepts of card managing of fixed assets in the Accounting subject which is marked by low activities, enthusiasm, and courage in expressing their ideas. The action is designed in two cycles; each cycle is done in one month. At the end of each cycle, the action carried out subsequent monitoring and evaluation of the results which is then reflected for the next cycle planning. The monitoring is done by using observation method, interview and test students understanding of the basic concepts of card managing of fixed assets in the accounting subject. After being given a lesson by using problem solving based learning method, students who do not understand the basic concept of card Managing of fixed assets shows a deeper understanding of the basic concepts of card managing offixed assets in Accounting subjects. Based on the evaluation results, it can be seen that in the first cycle there is an increase of student ability in mastering the basic concepts of card managing offixed assets in Accounting subject with the increase of students average scores of initial learning achievement of 59.40 to 68.72 with the percentage of mastery card managing of fixed assets in accounting subjects for 15.69%. Thus, the average percentage increases in the level of learning achievement in accounting before and after the first cycle of 29.61%. Meanwhile, after being given the action on the second cycle in the form of problem-solving techniques, the average score of students' achievement increases from 68.72 to 78.48 with the increas percentage of mastery card managing offixed assets in accounting subject for 13.92% this the increase of average percentage in the mastery card managing concepts of fixed assets in accounting subjects between cycle I and after cycle II is 29.61% (15.69% in the first cycle and the second cycle is 13.92%).